2016
DOI: 10.1007/s00406-016-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive symptoms and overall psychopathology in psychotic disorders: longitudinal assessment of patients and siblings

Abstract: The course of obsessive–compulsive symptoms (OCS) and its association with alterations in other clinical variables in patients with psychotic disorders is insufficiently known. Patients (n = 602) and unaffected siblings (n = 652) from the Dutch Genetic Risk and Outcome of Psychosis (GROUP) study were investigated at baseline and after 3 years. Participants were assigned to four groups based on the course of OCS over time: no-OCS, persistent OCS, initial OCS and de novo OCS. In addition to cross-sectional compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
(66 reference statements)
7
17
0
2
Order By: Relevance
“…The longitudinal results partly stand in line with results of previous analyses from the GROUP data, comparing OCS status groups and the course of PANSS and GAF scores [ 38 ] as well as cognitive functioning over the 3 year assessment period [ 37 ]. In all three studies at baseline, the group which was going to develop OCS at follow-up—the OCS de novo group—already showed more impairment than the no-OCS group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The longitudinal results partly stand in line with results of previous analyses from the GROUP data, comparing OCS status groups and the course of PANSS and GAF scores [ 38 ] as well as cognitive functioning over the 3 year assessment period [ 37 ]. In all three studies at baseline, the group which was going to develop OCS at follow-up—the OCS de novo group—already showed more impairment than the no-OCS group.…”
Section: Discussionsupporting
confidence: 86%
“…To study the course of OCS and its relationship with the course of motor symptoms both OCS and motor symptoms were categorized into four groups as was done in our previous analyses [ 37 , 38 ]: (1) a no symptom group, (2) a remission group, showing symptoms at baseline assessment only, (3) a de novo group, showing symptoms at follow-up, but not at baseline and (4) a persistent group, showing symptoms at both assessments. Subsequently, the relationship between those groups and motor symptoms was analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Negative childhood events (and especially serious parental disease or disability and conflicts within the childhood family) were related to obsessive-compulsive symptoms in males. In a Dutch study, psychosis patients with co-occurring obsessive-compulsive symptoms presented a more severe clinical picture and the authors discussed that the possible mechanisms could be increased sensitivity to stress, negative affectivity, and dysfunctional coping (Schirmbeck et al, 2016). An association between obsessive-compulsive disorder and psychosis has been established, indicating a shared etiological pathway (Cederlöf et al, 2015;Meier et al, 2014).…”
Section: Adversities and Symptomatologymentioning
confidence: 99%
“…Results indicate that patients with comorbid obsessive-compulsive symptoms suffer from more severe psychotic and affective symptomatology, which, in turn, leads to lower functioning and higher psychopathological burden. Furthermore, the authors found an association of symptom remission, suggesting that OCS, psychotic and affective symptoms functionally effect each other [5]. These two studies thus emphasize the importance of considering and integrating comorbidities in psychiatric research and, ultimately, clinical practice.…”
mentioning
confidence: 77%